The willingness to use internet-based home care services and its influencing factors among rural older people in Henan Province, China: a cross-sectional study - Yan, Yuwen; Zhang, Yan; Zhang, Huizhong; Li, Xizheng; Meng, Lixue; Tian, Yutong (Frontiers in Public Health, 2024)
Background To meet the growing health needs of older people, the Chinese government has introduced internet-based home care services. However, most rural older people have not yet benefited from such services, and the willingness to use these services and the factors influencing them remain unclear. Objective We aim to investigate the current willingness of rural older people to use internet-based home care services and analyze the factors. Methods We conducted a cross-sectional study across multiple centers using general information and self-developed questionnaires. Qualitative interviews, a literature review and the Delphi method were employed to develop the questionnaire. A total score of the questionnaire above 78 or higher indicates a high willingness to use internet-based home care services. Descriptive statistics, t-tests, one-way ANOVA, and multiple linear regression were used to explore the factors that influence the willingness of rural older people to use internet-based home care services. Results We surveyed 349 rural older people. The total score of rural older people’s willingness to use internet-based home care services was 84.49 ± 10.88, indicating high willingness, with the highest score for the dimension of perceived usefulness and lower scores for the dimension of perceived ease of use. Multiple linear regression analysis revealed that gender, education level, residence status, number of chronic diseases, and knowledge of internet-based home care services were the most important factors for rural older people (all p < 0.05). Conclusion The willingness of rural older people to use internet-based home care services is high. Thus, it is recommended that county hospitals increase public awareness of such services, optimize the design of their interfaces, and support family and social resources from relevant departments that can maximize access, so as to provide a reference for later relevant departments to enhance willingness.